The winner stands alone - Coelho, Paulo; Costa, Margaret Jull (Harper London, 2010)
At the Cannes Film Festival, a successful, driven entrepreneur goes to the darkest lengths to reclaim a lost love. Captured in all their crassness are producers, actors, aspiring starlets, supermodels, and notorious fashionistas, whose lives and actions hold sway over millions